PENGARUH ALOKASI DANA DESA, DANA DESA, BELANJA MODAL, DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP KEMISKINAN KABUPATEN/KOTA DI JAWA TIMUR - Nilam Indah Susilowati; Syamsul Hadi (Jurnal Ilmu Ekonomi JIE, 2017)
The purpose of this research was to analyze the Allocation of Village Funds, Village Funds, Capital Expenditures, and Gross Regional Domestic Product toward the level of poverty of a districts in East Java province. The analytical tool used was multiple regression with panel data, and then hypothesis testing with F test, and coefficient of determination (R2) at error rate a = 5% and t-table. The result of the regression analysis of panel data with selected model is Fixed Effect Model which shows that the variables of Allocation of Village Fund (ADD), Village Fund, Capital Expenditure and Gross Regional Domestic Product influence toward the level of poverty of a district / city with value respectively -3,59 for ADD, 2 , 87 for the Village Fund -6.05 for Capital Expenditure and -3.57 for the Gross Regional Domestic Product, whereas the coefficient of determination (R2) was 0.99 or 99%. This result shows that the variable of capabilities of Allocation of Village Funds, Village Fund, Capital Expenditure, and Gross Regional Domestic Product in explaining the village poverty was 99%.  Keyword: Allocation of Village Funds, Village Funds, Capital Expenditures, and Gross Regional Domestic Product, Poverty